The role of resistance training in the prevention of osteoporosis in postmenopausal women – a narrative review - Walczak, Klaudia; Wińska , Małgorzata; Bomze, Zuzanna; Dębkowska, Julia; Taraś, Aleksandra; Michułka, Klaudia (Journal of Education, Health and Sport, 2026)
Introduction: Postmenopausal osteoporosis is a common metabolic bone disease characterized by reduced bone mineral density (BMD) and an increased risk of fractures. Estrogen deficiency accelerates bone resorption, leading to progressive bone loss and impaired skeletal strength. Resistance training has gained attention as a non-pharmacological strategy for osteoporosis prevention due to its ability to stimulate bone remodeling through mechanical loading. Objective: To evaluate the effects of resistance training on bone mineral density, fracture risk, and musculoskeletal function in postmenopausal women based on current scientific evidence. Materials and methods: A narrative literature review was conducted using studies indexed in the PubMed database. Publications from 2015–2026 concerning resistance training and osteoporosis prevention in postmenopausal women were included. Earlier landmark studies were also considered when relevant. Results: The reviewed studies indicate that resistance training is an effective intervention for preventing postmenopausal osteoporosis. Most studies reported stabilization or modest increases in BMD, particularly in the lumbar spine and femoral neck. The effectiveness of training was influenced by exercise intensity, duration, and progressive overload. Moderate- to high-intensity, long-term programs produced the most favorable outcomes, whereas low-intensity or short-term interventions showed limited effects. Although evidence regarding fracture reduction remains inconclusive, improvements in muscle strength, balance, and fall prevention may indirectly decrease fracture risk. Conclusions: Resistance training appears to be a beneficial non-pharmacological approach for maintaining bone health in postmenopausal women. Regular participation may improve BMD and support fracture prevention. Further research is needed to establish standardized training protocols and optimize exercise recommendations.